Relationship between Periodontitis and Ischemic Cerebrovascular Disease - Magda Pinilla Pérez; Elisa DBeche Riambau; Miriam Castro Ortega (Revista Finlay)
Periodontitis is an immunoinflammatory disorder of microbial etiology caused by unique germs in the oral cavity that can spread through the bloodstream, activate the host's inflammatory response and promote the formation, maturation and exacerbation of atheromatous plaque. Several clinical studies have investigated the possible relationship between periodontal disease and diseases resulting from atherosclerosis such as ischemic heart disease and ischemic cerebrovascular disease. An exhaustive bibliographic review of scientific articles published in the databases: Pubmed, Medline, LILACS, Scielo, in the period between 2012 and 2022, in Spanish and English was carried out. The following were used as descriptors: periodontitis, cerebrovascular disease and atherosclerosis. The included reports indicate that cerebrovascular disease and atherosclerotic disease present the alterations with the greatest associations with periodontitis, however, larger studies are needed to determine the role of the severity and extent of periodontitis in these diseases.